Nitric Oxide Alleviates Salt Stress Inhibited Photosynthetic Performance by Interacting with Sulfur Assimilation in Mustard - Fatma, Mehar; Masood, Asim; Per, Tasir S.; Khan, Nafees A. (Frontiers in Plant Science, 2016)
The role of nitric oxide (NO) and sulfur (S) on stomatal responses and photosynthetic performance was studied in mustard (Brassica juncea L.) in presence or absence of salt stress. The combined application of 100 μM NO (as sodium nitroprusside) and 200 mg S kg−1 soil (S) more prominently influenced stomatal behavior, photosynthetic and growth performance both in the absence and presence of salt stress. The chloroplasts from salt-stressed plants had disorganized chloroplast thylakoids, but combined application of NO and S resulted in well-developed chloroplast thylakoids and properly stacked grana. The leaves from plants receiving NO plus S exhibited lower superoxide ion accumulation under salt stress than the plants receiving NO or S. These plants also exhibited increased activity of ATP-sulfurylase (ATPS), catalase (CAT), ascorbate peroxidase (APX) and glutathione reductase (GR) and optimized NO generation that helped in minimizing oxidative stress. The enhanced S-assimilation of these plants receiving NO plus S resulted in increased production of cysteine (Cys) and reduced glutathione (GSH). These findings indicated that NO influenced photosynthesis under salt stress by regulating oxidative stress and its effects on S-assimilation, an antioxidant system and NO generation. The results suggest that NO improves photosynthetic performance of plants grown under salt stress more effectively when plants received S.